Evaluation of IT Governance at Office X using the COBIT 5 Framework - Bayu, Krissna; Sudana, Oka; Wirdiani, Ayu; Paramartha, Ananda (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2021)
The IT governance audit aims to determine the level of importance (maturity level) of a company or government agency. IT governance audit is essential because if governance is not implemented correctly, the harmony between IT is beneficial to support business processes, and standard procedures will not be achieved. One of the agencies that require the implementation of good IT governance is Office X in Badung Regency. Office X in Badung Regency has a function in developing ICT infrastructure through application development, public service content, and ICT networks to improve public services. Conditions that occur in the field are frequent errors caused by internal and external parties that negatively impact the data management of Office X. The audit process begins with observations in the agency environment related to activity data and implementation, then mapping with business goals according to COBIT 5, followed by mapping business goals with IT Goals to obtain IT processes. The obtained IT processes are then selected to obtain critical IT processes according to the Executive Office. The audit results show that four IT processes need to be given recommendations for improvement, namely MEA 01, EDM 01, APO 07, DSS02.